Legal Protection of Midwives in Providing Health Services at Village Health Post - Fitri Andriana; Slamet Sampurno Soewondo; Sabir Alwi (Borong Newinera Publisher, 2021)
This study aims to identify and analyze the legal protection arrangements for midwives who work in the Poskesdes (Village Health Post) Majene Regency as well as the forms of implementation of legal protection for midwives who work in the poskesdes. The research method used is empirical research. The research location is in Majene Regency with a total sample of 41 poskesdes with regular categories spread over 8 districts, the types and sources of legal materials used are primary and secondary legal materials. Collection techniques through interviews, direct observation and literature study and then analyzed qualitatively and described to describe, describe and explain the results of the research. The author concludes that the implementation of health services at the poskesdes has not provided legal protection to midwives because midwives still carry out services that are not their authority and competence as a midwife. The implementation of legal protection through the delegation of authority is not in accordance with the regulations, the existing Standard Operating Procedures are not in accordance with the conditions of the Poskesdes facilities and the guidance and supervision system for midwives has not been maximally implemented.